Stock Price Fluctuations and Corporate Forecasts Disclosure: Evidence from an Emerging Market - Kasgari, Abbas Bagherian; Sheykhi, Keyvan (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2014)
This research investigates the relation between forecasting report disclosure and stock price fluctuations. The first hypothesize examine if there is a relation between two variables among companies which lead to fluctuation in the stock price and the second hypothesize examined these variables over research industries. Capital market reacts to new information in most cases- at least one month before the official date of the disclosure. We found evidence of fluctuation in stock prices before disclosure indicate that information was released to the market before official disclosure. In the other word, stock prices react to the unofficially released information and rumors to the market around the releasing new officially disclosure date. This fraudulent attempt was initiated by price manipulation in cases which we don’t see significant price change during forecasted disclosure even if there are significant change in reported earning values. This investigation indicates that there is a significant relationship between releasing forecasted information and stock price fluctuations in the selected listed companies in TSE.